The Difference Between Magnetism and Gravity - Eid, Salah (Advances in Social Sciences Research Journal, 2020)
The circular motion is composed of two halves: equal in magnitude and opposite in direction. In magnetism the two halves are separated from each other, where there is an attraction between opposites and a repulsion between likes, the circular motion here is opened. In gravity the circular motion is closed where the two equal and opposite halves of the circular motion are joined together directing every point to the center of the motion. In gravity always attraction, and no repulsion.